How Indigenous Nation-Building Can Strengthen Indigenous Holistic Health Outcomes: Retelling the Right to Health - McMillan, Mark; McMillan, Faye; Rigney, Sophie (Umeå University Library, 2017)
The United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP) has declared that Indigenous peoples and populations inherently possess a right to health. Such a right does not merely exist with reference to physical health. The General Assembly of the United Nations when adopting the UNDRIP requires the meaning of “health” to be expansive and also be characterised as a collective right. This article will provide a particular framework for understanding the right to health for Indigenous peoples as a collective right, which exists in a symbiotic relationship with the rights to greater self-determination and governance.